1991
DOI: 10.1046/j.1537-2995.1991.31491213295.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion costs: a multicenter study

Abstract: The cost of delivering a unit of blood (whole blood or red cells) to a hospitalized patient was examined in 19 United States teaching hospitals. The average hospital acquisition cost was calculated by using the prices charged by regional blood centers for blood products. To this cost was added an estimate of costs incurred by hospitals for handling, testing, and administering blood. Across study sites, the average hospital cost per unit transfused was $155 and the average charge to the patient was $219. Acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(70 citation statements)
references
References 5 publications
0
70
0
Order By: Relevance
“…Furthermore, the blood transfusion economics has not been addressed in any of these studies. A multicentre study on blood transfusion cost performed in 1991 27 revealed the average hospital cost per unit transfused was $155 which would be far higher now. It is therefore evident from this meta-analysis that LADG have biological, immunological and economical benefits for the patient and the health care system by reducing peri-operative transfusion needs.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the blood transfusion economics has not been addressed in any of these studies. A multicentre study on blood transfusion cost performed in 1991 27 revealed the average hospital cost per unit transfused was $155 which would be far higher now. It is therefore evident from this meta-analysis that LADG have biological, immunological and economical benefits for the patient and the health care system by reducing peri-operative transfusion needs.…”
Section: Discussionmentioning
confidence: 97%
“…A threshold of 10,000/l may be used in patients undergoing induction therapy for acute leukemia [27] or severely thrombocytopenic bone marrow transplant patients [13,31,32]. These efforts may result in cost savings and improved treatment for patients [33]. In addition, computer-assisted programs currently exist that allow tracking and analysis of blood component use to monitor the implementation of platelet transfusion recommendations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Both, blood loss and transfusion of blood can jeopardize patient health via cardiovascular incidents, infection or allergic reactions [12] and add to significant costs to the health care system [13]. The reduction of perioperative blood loss and the reduction of transfusion requirements in primary TKA should be a clinical priority.…”
Section: Introductionmentioning
confidence: 99%